Investigation of the electron transport layer in semitransparent organic photovoltaic cells using near-infrared light-absorbing materials. (25th June 2021) - Kuwano, Kohei; Okajima, Taiki; Watanabe, Yasuyuki; Chikamatsu, Masayuki; Yoshida, Yuji; Nishikawa, Eiichi
Abstract: One challenge to realizing semitransparent organic photovoltaic (ST-OPV) cells is achieving both a high transmittance and high power conversion efficiency (PCE) simultaneously. We investigated the effect of using near-infrared light-absorbing materials in the different electron transport layer materials. Two materials were considered: zinc oxide (ZnO), which is used in conventional OPV cells, and tin oxide (SnO2 ), which has gained recent interest for its deposition at low temperatures suitable for flexible substrates. Experimental results showed that the ZnO- and SnO2 -based ST-OPV cells had PCEs of 5.60% and 6.71%, respectively. The thickness of the organic active layer was varied to increase the transmittance in the visible light range. The SnO2 -based ST-OPV cells were optimized to a thickness of 90 nm, which resulted in a PCE of 5.91%, average visible transmittance of 22.37%, and light utilization efficiency of 1.32%.